2014
DOI: 10.1016/j.chembiol.2014.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Sulfated Glycosaminoglycans Control the Extracellular Trafficking and the Activity of the Metalloprotease Inhibitor TIMP-3

Abstract: SummaryTissue inhibitor of metalloproteinase 3 (TIMP-3) is an important regulator of extracellular matrix (ECM) turnover. TIMP-3 binds to sulfated ECM glycosaminoglycans or is endocytosed by cells via low-density lipoprotein receptor-related protein 1 (LRP-1). Here, we report that heparan sulfate (HS) and chondroitin sulfate E (CSE) selectively regulate postsecretory trafficking of TIMP-3 by inhibiting its binding to LRP-1. HS and CSE also increased TIMP-3 affinity for glycan-binding metalloproteinases, such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
63
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(70 citation statements)
references
References 52 publications
5
63
1
1
Order By: Relevance
“…This is provided by an sHA1-induced pronounced increase of different MMP inhibitors to decrease the overall ECM degradation. Among those, TIMP3, which is the only one among four TIMPs that is tightly anchored in the pericellular matrix, interacts with sulfated GAG as shown for heparin and chondroitin sulfate (79,80). As shown before, after sHA1 exposition most prominent regulated proteins were found in biological function of cell-matrix interaction, ECM organization, and regulation of growth factor bioavailability (Fig.…”
Section: Comparison Of the Matrix Vesicle Proteome With Hbmsc Proteomementioning
confidence: 64%
“…This is provided by an sHA1-induced pronounced increase of different MMP inhibitors to decrease the overall ECM degradation. Among those, TIMP3, which is the only one among four TIMPs that is tightly anchored in the pericellular matrix, interacts with sulfated GAG as shown for heparin and chondroitin sulfate (79,80). As shown before, after sHA1 exposition most prominent regulated proteins were found in biological function of cell-matrix interaction, ECM organization, and regulation of growth factor bioavailability (Fig.…”
Section: Comparison Of the Matrix Vesicle Proteome With Hbmsc Proteomementioning
confidence: 64%
“…2). In this regard, Troeberg et al [49] reported that endocytic removal of TIMP-3 was inhibited by heparin, heparan sulfate proteoglycans and chondroitin sulfate E, making TIMP-3 available for metalloproteinase inhibition. In addition, the sulfated GAG-TIMP-3 complex has higher affinity for ADAMTS-4 and ADAMTS-5 than TIMP-3 alone, but the sulfation pattern of the GAG is crucial for this activity.…”
Section: Ectodomain Shedding Of Lrp1mentioning
confidence: 97%
“…GAGs increase TIMP-3 affinity for MMP-2, − 7 [46], ADAMTS-2 [47], ADAMTS-4 and ADAMTS-5 [48], and this is likely to be the case for other sulfated GAG-binding metalloproteinases. Notably, the ability of sulfated GAGs to increase the affinity between TIMP-3 and ADAMTS-4 and ADAMTS-5 is highly dependent on the sulfation pattern of the GAG [49].…”
Section: Regulation By Locationmentioning
confidence: 99%
“…13 Little free TIMP-3 is present in tissues since it binds tightly to sulfated oligosaccharides in the ECM and is also endocytosed by cells after it has been secreted. 16,17 Hyaluronic acid hydrogel was used to encapsulate recombinant human TIMP-3, to which it binds through electrostatic interactions, allowing slow release in vivo. In pigs, MI was induced by coronary ligation, and the hydrogel/ TIMP-3, hydrogel alone, or saline was injected into the MI region in subgroups.…”
Section: 15mentioning
confidence: 99%